Salinity intrusion and disaster resilience in coastal agriculture: Impacts and adaptation strategies in Bangladesh - Shib Pado Bairagi; Md. Faisal; Protus Roy Hridoy (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: Salinity intrusion is a major environmental challenge in the coastal region of Bangladesh, threatening agricultural production, fisheries, livestock, and rural livelihoods. This study aimed to assess the causes and impacts of salinity intrusion on crop production, fisheries, and livestock, and to identify local adaptation strategies adopted by farmers in Baradal Union of Assasuni Upazila, Satkhira District. Methods: Primary data were collected through household surveys of 150 respondents and five key informant interviews (KIIs), complemented by secondary information from published literature and official reports. A purposive sampling technique was used, and the findings were analysed descriptively. Findings: The results revealed that the Kholpetua River is a major source of salinity intrusion, with more than 75% of respondents identifying it as the primary driver of increasing salinity in soil, surface water, and groundwater. Riverbank erosion and tidal flooding further exacerbate salinity levels, particularly during the dry season. Salinity has significantly reduced soil fertility, limited crop diversification, and adversely affected rice, vegetable, livestock, and freshwater fish production. Native freshwater fish species have declined substantially, while sheep and goat populations have decreased due to freshwater scarcity, fodder shortages, and disease prevalence. Farmers have adopted several adaptation measures, including salt-tolerant crop varieties, rainwater harvesting, crop calendar adjustment, raised-bed cultivation, and soil amendments. However, inadequate institutional support, limited technical knowledge, financial constraints, and governance-related barriers continue to hinder effective adaptation. Conclusion: Strengthening freshwater management, riverbank protection, climate-resilient agricultural practices, and farmer training programs is essential for enhancing resilience to salinity intrusion in coastal Bangladesh. Novelty/Originality of this article: This study provides a location-specific empirical assessment of the agricultural and livelihood impacts of salinity intrusion in Baradal Union and documents locally practiced adaptation strategies and barriers. The findings provide evidence to support locally appropriate adaptation planning and policy development in salinity-prone coastal areas.